Analisis Pengaruh Geometri Peledakan Terhadap Fragmentasi Hasil Peledakan Serta Digging Time Dan Produktivitas Alat Gali Muat Pada Tamka PT. Allied Indo Coal Jaya, Kota Sawahlunto - Rahadiyan Malvin Sunyoto; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The overburden disassembly process implemented by PT. Allied Indo Coal Jaya is by drilling and blasting. Observations in the field of actual blast geometry applied by the company obtained fragmentation of boulder-sized blasting results with a percentage of + 31%. The large percentage of boulders resulted in the diggability of the loading and unloading tools and the company's planned load digging productivity target of 100 bcm/hour was not achieved. The study aims to design optimum blasting geometry to reduce the percentage of boulders so that loading activities become effective and the productivity of loading tools increases. The research method was carried out by providing recommendations for blasting geometry based on R.L. Ash theory and the method